Facet Control for Trap‐State Suppression in Colloidal Quantum Dot Solids. (6th April 2020) - Xia, Yong; Chen, Wei; Zhang, Peng; Liu, Sisi; Wang, Kang; Yang, Xiaokun; Tang, Haodong; Lian, Linyuan; He, Jungang; Liu, Xinxing; Liang, Guijie; Tan, Manlin; et al.
Abstract: Trap states in colloidal quantum dot (QD) solids significantly affect the performance of QD solar cells, because they limit the open‐circuit voltage and short circuit current. The {100} facets of PbS QDs are important origins of trap states due to their weak or missing passivation. However, previous investigations focused on synthesis, ligand exchange, or passivation approaches and ignored the control of {100} facets for a given dot size. Herein, trap states are suppressed from the source via facet control of PbS QDs. The {100} facets of ≈3 nm PbS QDs are minimized by tuning the balance between the growth kinetics and thermodynamics in the synthesis. The PbS QDs synthesized at a relatively low temperature with a high oversaturation follow a kinetics‐dominated growth, producing nearly octahedral nanoparticles terminated mostly by {111} facets. In contrast, the PbS QDs synthesized at a relatively high temperature follow a thermodynamics‐dominated growth. Thus, a spherical shape is preferred, producing truncated octahedral nanoparticles with more {100} facets. Compared to PbS QDs from thermodynamics‐dominated growth, the PbS QDs with less {100} facets show fewer trap states in the QD solids, leading to a better photovoltaic device performance with a power conversion efficiency of 11.5%. Abstract : The {100} facets of ≈3 nm PbS quantum dots (QDs) are minimized by tuning the balance between the growth kinetics and thermodynamics in the synthesis. Compared to PbS QDs from thermodynamics‐dominated growth, the PbS QDs with less {100} facets show fewer trap states in the QD solids, leading to a better photovoltaic device performance with a power conversion efficiency of 11.5%.